دلالات المجاز المرسل في شواهد قرآنية = The significant of al-Majāz al-Mursal in the Qurʾānic instances = Makna-makna yang tersirat di sebalik al-Majāz al-Mursal di dalam beberapa contoh ayat al-Qur’ān al-Karīm - Mokhtar, Maahad; Ahmed Hussien, Nasreldin (IIUM Press, International Islamic University Malaysia, 2020)
لا يُستحسن التّعبير المجازيّ إلّا إذا كان أبلغ من التّعبير الحقيقيّ. والمجاز المرسل وجه من وجوه التّعابير المجازيّة. ومن الملاحَظ أنّ الجهود السّابقة في دراسة المجاز المرسل في القرآن الكريم تنحصر في الإشارة إلى وروده في الآيات القرآنيّة الكريمة وعلاقاته دون بيان دلالاتها بالتّفصيل؛ وعلى سبيل المثال: لماذا يكون التّعبير المجازيّ في قوله تعالى: ﴿ وَاسْأَلِ الْقَرْيَة الَّتِِ كُنَّا فِيهَا ﴾ 1 أبلغ من التّعبير الحقيقيّ "واسأل أهل القرية التِ كنّا فيها"؟ ما الدّلالة الّتِ يحملها التّعبير المجازيّ في المجاز المرسل هنا ما لا يحملها التّعبير الحقيقيّ؟ فللإجابة عن مثل هذا السّؤال، يسعى البحث إلى دراسة دلالاتٍ للمجاز المرسل في شواهد قرآنيّة؛ ما يُسهم في الفهم العميق لهذا الوجه من وجوه البيان القرآنيّة البليغة. توصلت الدراسة إلى أنّ الوجه البيانيّ يحمل دلالات متعدّدة جاءت ضمنياً؛ ما يجعل التّعبير المجازيّ في تلك الشّواهد أبلغ من التّعبير الحقيقي، وأن تلك الدّلالات جاءت إمّا لبيان أمور أو حكم أو شعور أو تصوير أمرين في آن واح د؛ ما يبرهن على كون المجاز المرسل وسيلة من وسائل البيان القرآني البليغ. ********************************************************* It is well learned in the Science of al-Bayān that ta’bīr majāzi (figurative expression) will be employed and considered admirable only if it could bring about a significant meaning. There are many types of ta’bīr majāzi in Arabic rhetorical sciences and one of them is known as al-Majāz al-Mursal. Previous attempts to find out the occurrences of al-Majāz al-Mursal in the Holy Qurān have been observed to be confined to referring those occurrences of al-Majāz al-Mursal in the Qurānic verses to their relations but tended to overlook the significance of its use. For instance, it is pointed out that al-Majāz al-Mursal occurs in Surah Yusuf verse 82 which means ʻʻand ask the town where we have been…ʼʼ and al-Majāz al-Mursal here has been referred to a relation known as al-maḥalliyyah which means ʻʻto mention a place but what is really meant from it is to refer somebody who occupies that placeʼʼ. Thus, the interpretation of the verse: ʻʻand ask the (people of the) town where we have been…ʼʼ However, the significant of al-Majāz al-Mursal here has not been elaborately explained. Why is the figurative expression: ʻʻand ask the town..ʼʼ employed and considered admirable in this verse instead of the actual expression ʻʻAnd ask the people of the town..ʼʼ ? It is obvious that the question is meant to be directed to ʻʻthe people of the town..ʼʼ and not ʻʻthe townʼʼ itself. However, since the expression ʻʻask the town..ʼʼ is considered as figurative expression, its significant has to be explained intricately so that the wisdom of its occurrence could be comprehended. Thus, the question that should be asked here is that: What is the significant of figurative expression ʻʻask the townʼʼ here and why is it preferable to the actual expression ʻʻask the people of the townʼʼ? Therefore, this research attempts to find out the significations of al-Majāz al-Mursal in the Holy Qurʾān in order to enhance the understanding of the subtleties of this feature of Qurʾānic style. The study concludes that the aspect of eloquence has several meanings that come implicitly; the very characteristic that makes figurative expression more eloquent from the real expression. Those meanings are either to explain matters, judgement, feeling, or description of two situations simultaneously; a strong indication that the al-Majāz al-Mursal is one of the most effective Quranic eloquence tools. ************************************************************************* Di dalam ilmu al-Bayān, ta‘bīr majāzī (ungkapan kiasan) hanya boleh diterima dan digunapakai sekiranya ia membawa makna yang signifikan. Terdapat pelbagai jenis ta‘bīr majāzī. Salah satu daripadanya al-Majāz al-Mursal. Para sarjana telah banyak mengkaji al-Majāz al-Mursal. Namun, kajian yang dilakukan hanyalah sekadar mencakupi contoh-contoh ayat Qur’ān yang mengandungi al-Majāz al-Mursal sahaja tanpa menekankan kepentingan makna yang tersirat di dalamnya. Sebagai contoh, al-Majāz al-Mursal yang terkandung dalam ayat 82 Surah Yusuf yang bermaksud : “ Dan bertanyalah kepada negeri yang pernah kami tinggal…”. Al-Majāz al-Mursal yang berlaku dalam ayat ini merujuk kepada hubungan yang dikenali sebagai al-maḥalliyyah yang bermaksud “menyebut suatu tempat tetapi yang dimaksudkan sebenarnya adalah orang yang berada di tempat tersebut”. Oleh itu, ayat tersebut ditafsirkan sebagai : “Dan bertanyalah kepada (penduduk) negeri yang kami pernah tinggal…”.Namun, kepentingan penggunaan al-Majāz al-Mursal tidak diperjelaskan secara terperinci. Persoalan yang boleh dikemukakan ialah mengapa ungkapan kiasan “Dan tanyalah kepada negeri…” diguna dalam ayat ini berbanding ungkapan biasa; “Dan bertanyalah kepada penduduk negeri…” ? sedangkan sudah jelas bahawa pertanyaan itu diajukan kepada “penduduk negeri itu..” bukan kepada “negeri itu” sendiri. Oleh kerana ungkapan “Dan bertanyalah kepada negeri..” dianggap sebagai ungkapan kiasan, kepentingan maksud al-Majāz al-Mursal dalam ayat tersebut haruslah diperjelaskan secara terperinci supaya dapat difahami kewajaran penggunaanya dan mengapa ia lebih diutamakan berbanding ungkapan biasa. Kesimpulannya, kajian ini dilakukan bagi mendalami kepentingan makna al-Majāz al-Mursal dalam Kitab Suci al-Qur’ān untuk meningkatkan pemahaman terhadap makna yang tersirat di sebaliknya.